Recycled Material as a Conductive Polymer for Volatile Organic Compound (VOC) Sensor - Supri, A. Ghani, Dr.; Salmah, Husseinsyah, Dr. Ir.; Ali Yeon, Md. Shakaff, Prof. Dr.; Abu Hassan, Abdullah; Ammar, Zakaria; Heah, Cheng Yong (Malaysian Invention and Design Society (MINDS), 2010)
Dr. Supri A. Ghani and his team won silver at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 di Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.